Management of iron deficiency anemia in Indian women using ferric carboxymaltose: a sub-group analysis from the PROMISE multi-center real-world study in India - Gudidevuni, Jamunadevi; Shah, Jignesh; Kulkarni, Ketan; Tope, Rutuja; Katke, Prashant; Suryawanshi, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To evaluate the effectiveness of intravenous ferric carboxymaltose (FCM) in patients with iron deficiency anaemia (IDA) across 269 centres in India, we conducted a retrospective, observational, real-world investigation. The present analysis was done to evaluate FCM in Indian women with IDA in a real-world scenario. Methods: Haematological parameters were examined for the study population’s baseline and 4±1 week follow-up data on females with anaemia who regularly received FCM for anaemia management. Results: 1666 females with IDA, the hematological parameters improved significantly at 4 weeks (p<0.001) Hb increased by 2.78 g/dl, serum ferritin increased by 35.26 µg/l, haematocrit, red blood cell (RBC) count, mean corpuscular haemoglobin (MCH) and mean corpuscular volume (MCV). Subjects with severe IDA (n=304), significant increase in Hb (by 3.32 g/dl), serum ferritin (by 34.96 µg/l) (p<0.001 for both), RBC count (p<0.001), haematocrit (p=0.004), MCH (p<0.001) at 4 weeks. Subjects with moderate IDA (n=1227), significant increase in Hb (by 2.66 g/dl), serum ferritin (by 35.42 µg/l), haematocrit, RBC count, MCH and MCV (p<0.001 for all) at 4 weeks. Subjects with mild IDA (n=26), significantly higher mean Hb values were seen at 4 weeks (by 1.99 g/dl) Hematological parameters improved compared to baseline at 4 weeks mean difference was statistically insignificant. Physicians rated efficacy and safety of FCM as very good to good in 97.4% and 97.1% of subjects, respectively. Conclusions: FCM corrects anemia in all subsets of Indian women in short span of 4 weeks and thus supports evidence of efficacy and safety.